(untitled) (Journal of Hama University, 2022)
The study aimed to assess Organizational Justice by Nursing Staff, and determine its Relationship to the organizational commitment of the nursing staff at Tishreen University Hospital in Lattakia. The sample consisted of (200) nurses working at Tishreen University Hospital city, who were presented during the data collection period (convenience sample).The researcher used a questionnaire to assess organizational justice that was used by the researcher Alian (2016) in his study on organizational justice, and a questionnaire to assess organizational commitment that was used by the researcher Salman (2013) in his assessment of the organizational commitment. to collect data related to the study, and after unloaded the data, it was statistically processed and tabulated using the SPSS statistical program version (20.( The most important results of the study were: that the level of organizational justice for the nursing staff (the study sample) as a whole was weak, while the level of organizational commitment of the nursing body (the study sample) as a whole was average, there is no positive moral statistically significant relationship between organizational justice and organizational commitment.